THE INFLUENCE OF DISCIPLINE, ABILITY, AND COMPENSATION ON EMPLOYEE PERFORMANCE AT THE CULTURAL OFFICE OF THE RIAU ISLANDS PROVINCE - Atik, Atik; Khaddafi, Muammar; Satriawan, Bambang; Indrayani, Indrayani (CV. Radja Publika, 2022)
Reliable and quality human resuorces play a major role in the prosess of improving performance with one example that is applied to improving work productivity. Performance is influenced by various factors, both related to the workforce it self and other factors such as education, skills, discipline, attitudes and work ethics, motivation, nutrition and health, level of income, social security, environment and work climate, job opportunities, and achievement opportunities. In this study to prove the effect of discipline, ability and compensatioan on the performance of the employees of the Riau Islands Province Cultural service. The populations in this study were employees of the Riau Islands Provincial Culture Office in Tanjungpinang, with a total sample of 72 people.